Male and Female Instructors’ Instructional Talks in Indonesian College EFL Classrooms: Case Study of Vocational Higher Education in South Sulawesi - Surya Dewi; Syamsidar Syamsidar; Lily Dianafitry (Journal La Edusci, 2020)
It is believed that men are different from women in communicating their ideas and feelings through the communication system called language. This article divulges how gender factor influences EFL instructors’ instructional talks in Indonesian context. It goes over findings of a case study undertaken at two colleges in Makassar, South Sulawesi. In the study, four EFL instructors (two male and two female) of the colleges were purposively chosen as the subjects, and the data leading to the findings were obtained through classroom observation. The findings reveal that the male instructors’ instructional talks are quite stiff and typically stimulate instructor-centered atmosphere, while the female instructors’ are more genial and naturally stimulate instructor-students harmonious interactive communications. Thus, it can be inferred that while the male instructors tend to be ‘commanders’ in front of the class, the female set themselves as amicable “mothers” to the students.